Chapter 6 Ageism and Age Discrimination in the Labour Market: A Macrostructural Perspective (2018)
This chapter looks at the phenomenon of ageism and age discrimination in the labour market from a socio-political perspective and draws attention to key factors in its emergence. The approach adopted here goes beyond the individualistic and micro accounts adopted mostly by psychologists, as well as beyond the meso perspective as used in organisation and work environment studies. Our aim is rather to examine the role of macrostructural processes and transformations and to identify their link to the persistence of ageism and age discrimination in contemporary labour markets. First, an overview of the most predominant conceptual understandings of ageism and age discrimination in employment are provided, which clarify the theoretical and empirical distinctions between the two related, but not synonymous, concepts. This section also provides a life-course perspective on age discrimination in the labour market by looking at experiences of different age groups, as well as an elaboration of the intersectional approach to ageism. Second, the chapter investigates the dynamics between the phenomena of ageism and age discrimination and a range of socio-political contexts, cultural settings, and legal and economic conditions. We then discuss the costs and consequences of age discrimination in employment, as well as particular policy responses.